2011
DOI: 10.1097/brs.0b013e3181f822c7
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Evaluation of the Cervical Spondylotic Myelopathy With Flexion-Extension Magnetic Resonance Imaging

Abstract: Cervical spondylotic myelopathy results from the synergistic action of static and dynamic factors, the latter of which play an important role. In some patients, IHIS on T2 images is only visible with the neck in flexion. That might explain why IHIS is first detected after surgery in some patients in whom MRI was obtained before surgery only in the neutral position. Dynamic MRI is useful to determine more accurately the number of levels where the spinal cord is compromised, and to better evaluate narrowing of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
87
2
9

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(101 citation statements)
references
References 23 publications
2
87
2
9
Order By: Relevance
“…Spinal alignment may contribute to the development of such MRI abnormality, with an increasing SVA correlating with greater T2 signal abnormality among patients with kyphosis but not among those with lordosis. Certainly, dynamic compression in CSM has been depicted using fl exion-extension MRI [13][14][15] and Zhang et al 14 demonstrated that the cervical spinal canal diameter is least in extension and that in a subset of patients with CSM, T2 hyperintense intramedullary signal changes are only seen in the fl exion MRI condition. Yu et al 13 have described that segmental hyperextension greater than 10º and increased range of motion are associated with T2 hyperintense intramedullary changes.…”
Section: Discussionmentioning
confidence: 99%
“…Spinal alignment may contribute to the development of such MRI abnormality, with an increasing SVA correlating with greater T2 signal abnormality among patients with kyphosis but not among those with lordosis. Certainly, dynamic compression in CSM has been depicted using fl exion-extension MRI [13][14][15] and Zhang et al 14 demonstrated that the cervical spinal canal diameter is least in extension and that in a subset of patients with CSM, T2 hyperintense intramedullary signal changes are only seen in the fl exion MRI condition. Yu et al 13 have described that segmental hyperextension greater than 10º and increased range of motion are associated with T2 hyperintense intramedullary changes.…”
Section: Discussionmentioning
confidence: 99%
“…As such, the pathologist's opinion of the significance of histopathologic changes in the context of a history or clinical signs is akin to a clinician's use of history and other clinical information in assessing the significance of perceived deficits detected during subjective (neurologic) examination (ie, expectation bias being a positive discriminatory factor). Furthermore, the assumption that all horses with apparent neurologic gait deficits should have identifiable pathologic changes might well be flawed as dynamic functional deficits might occur with only intermittent spinal compression, as is believed to occur in humans 46. In addition, recent identification of an important genetic component in controlling gait in horses47 reveals the extent to which gait alterations can have a functional rather than pathologic basis.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with multilevel disease with associated subclinical instability brought out in dynamic radiographs can be dealt with by this procedure, 3. Fusion decreases the chance of dynamic compression due to repetitive microtrauma that is known to occur in CSM, [11,19] 4. As laminoplasty is known to cause worsening of axial neck pain, laminectomy with lateral mass fusion may be preferable in patients with multilevel disease with signifi cant neck pain preoperatively, [20] 5.…”
Section: Laminectomy With Lateral Mass Fusionmentioning
confidence: 99%